Offender agency at sentencing: exploring the grounds and scope for engaging offenders in the determination of punishment - Maes, E (2019)
Punishment is a grave intrusion into individual liberty, yet in most liberal criminal justice systems, including England and Wales, those punished are rarely directly engaged in determining their sentence. The thesis challenges this status quo and asks on what grounds and to what extent offenders should exercise agency at sentencing, and to what extent offenders can exercise agency in current English sentencing practice. First, it examines possible theoretical arguments for offender agency on a state-centred account of sentencing. It does so in respect of several theories of punishment: communicative variations of desert theory, a forgiveness-based theory of punishment, and therapeutic jurisprudence. Secondly, the thesis develops a normative framework for offender agency. It argues that there may be good justifications for allowing offenders to exercise agency at sentencing, to be more respectful of the offender as a responsible moral agent and to foster rehabilitation. It explores conceptually what an ‘agentic’ sentencing system might entail and argues it should be based on the paradigm of a dialogue between the judge and offender. The offender’s agency should be non-dispositive and in principle should have no guaranteed determinative influence on the sentence. However, the offender’s input may alter the disposition, insofar as it is aligned with the public interest. It explores other constraints on offender agency to preserve the state’s fundamental role in sentencing. The proposed model embodies a different conception of sentencing as a decision-making process to be done with offenders, rather than to offenders. The thesis examines objections that could be levelled against an agentic sentencing model. Finally, the thesis undertakes a doctrinal enquiry into instances of offender agency in current English sentencing practice. It concludes that, while current sentencing practice does not respect offender agency in a principled manner, there is both value in and scope for allowing offenders to exercise agency in a state-centred sentencing system.